Critical discourse analysis in patriarchal society: Covid-19 and increased women workload - Khirjan Nahdi; Muh. Taufiq; Dukha Yunitasari; Samsul Lutfi; Suhartiwi Suhartiwi; Usuludin Usuludin; Roni Amrulloh (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2021)
By utilizing discursive theory, social actors, and sociosemantics, this study aims to find the increase in women's working hours, reasons, and causality between working hours, types of work, and their respective recognition in social relations. The study used a qualitative descriptive method, with research data focusing on the context before and during COVID-19. Data were collected through online surveys and interviews. Data analysis was carried out based on sociosemantic analysis in Critical Discourse Analysis (CDA), starting with calculating working time, reasons, and causality according to the CDA. The research findings show that women's working hours when COVID-19 has increased accumulatively. The accumulative increase relates to all types of work when COVID-19 requires women's access. Respondents admitted that everything was done as a custom for reasons of fate, obligations and traditions. It can be concluded that, there is a causality between working hours, type of work and respondents' reasons that prevalence occurs due to cognitive involvement, religion, and tradition. CDA views the context of this imbalance in this relationship as a social problem. Problem solving according to the CDA can be done through an educational process, with the assumption of solving problems for the future.